Internationalisation of Higher Education in Malaysia: Transformation, Economic Impact, Policies and Strategies - Chee, Diana Sheau Jen (2010)
Internationalisation is a phenomenon that has occurred since the 13th century, while what we see today is the extension of internationalisation into the higher education sector through the forces of globalisation, which has accelerated changes in diversification, expansion, privatization, marketization of higher education.This paper is an attempt to review the transformation of internationalisation of higher education in Malaysia and discuss the trends of the internationalisation of Malaysian Higher Education Institutions (HEIs). Global views on local contextual perspectives, concepts on internationalisation, strategies, and rationales behind Malaysia‘s internationalisation, and the roles of Malaysia government and HEIs are also discussed.Interviews were conducted with internationalisation officers from Malaysian HEIs, Ministry of Higher Education (MOHE), peripheral industry and local and international students in Malaysia in the form of individual interviews and focus groups. The aim of the study is to evaluate the estimated increase in Malaysia‘s economic activities caused by the nternationalisation of HEIs in Malaysia. Literature on the topic, as well as the results of the interviews conducted, were then analyzed together with the changing trends and economic impact of internationalisation, which led to the quest for a set of indicators. The later part of the paper describes an analysis of the policies by the government in Malaysia that supports the internationalisation in HEIs. It describes the strategies suggested by government‘s Performance Management and Delivery Unit (PEMANDU) for the development of education in the country.Finally, while internationalisation has contributed so much to the Malaysian economy, it has highlighted several concerns for the country. It has led to the questions on policies and facilities for aggressive recruitment activities and mass enrolments of international students. The future economic, social and spiritual well-being of Malaysia depends vitally on the success of this transformation in higher education. The importance of higher education in this process must not be underestimated. It is a critical agenda in the formulation of national policies.